(3GdBdjGJ GdLOjOI ddJbGYO aj Xd GdJMhdGJ GdEbJUGOjI GdQGgfIs - (3edjcI(B, (3eMOjOs ((3JdeSGf(B:s (3GdecJH GdLGeYj GdMOjK,s, 2017)
(3jVe eONd ddJCejf hGbJUGOjGJ GdJCejf GdLGeYj, OQGSI fXGe GdVeGf GdGLJeGYj hGdJbGYO aj GdLRGFQ, GdfXGe GdGbJUGOj hBKGQg Ydi efXheI GdJbGYO aj GdLRGFQ, JWhQ fXGe GdJbGYO aj GdTQcI GdhWfjI ddJCejfGJ ef GbJUGO eQcRj Edi GbJUGO GdShb, GdBdjGJ GdLOjOI GdecedI ddJbGYO aj GdLRGFQ, GUdGM hCaGb fXGe GdJbGYO aj GdTQcI GdhWfjI ddJCejfGJ(BSAAs
(3HHdjhZQGajG(B: (3U(B.326-335 (3GdedGMb U(B.293s
Keywords: (3GdJCejf GdELJeGYj(B- (3GdLRGFQs; (3TQcGJ GdJCejfs